Booklet, Strip Comic, and Quartet Card(BOSQUE) Intervention in First Aid Education for Choking Toddlers - Setya Rini, Puji (Sahabat Publikasi Kuu, 2025)
Introduction: Choking is one of the leading causes of accidental death in toddlers, which can be prevented through first aid education. Unfortunately, mothers' knowledge of choking management is still low, and conventional education methods are uninteresting and difficult to understand. Therefore, innovative educational media is needed to effectively improve mothers' understanding. Methods: This study used a pre-experimental quantitative design with a one-group pretest-posttest approach. The sample consisted of 31 mothers with toddlers at Aisyiyah 11 Kindergarten in Palembang, selected using total sampling. The intervention was carried out by providing health education using BOSQUE media, which consisted of booklets, comic strips, and quartet cards. The data were analyzed using the Wilcoxon test because the data were not normally distributed. Results: The results showed a significant increase in mothers' knowledge after the intervention. The median knowledge score before the intervention was 9.00 and increased to 15.00 after the intervention. The Wilcoxon test showed a p-value of 0.001 (p < 0.05), which means there was a significant difference between before and after the intervention. Conclusion: The BOSQUE media was effective in increasing mothers' knowledge of first aid for choking in toddlers. This media can be used as an alternative form of public health education that is fun, interactive, and easy to understand, especially for groups of mothers with low to medium levels of health literacy.